Ukraina rahvusväeosade loomine Vene armees 1917. aastal [The Creation of Ukrainian National Military Units Within the Russian Army in 1917] - Rukkas, Andrii (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2018)
This article is devoted to the process of the formation of Ukrainian national units within the Russian Army aft er the February revolution.In February 1917, the monarchy was overthrown in Russia and the Provisional Government came to power. The revolutionary wave touched the Russian army, where almost four million Ukrainians were serving at the time. On 9 March, the great meeting of Ukrainian officers and soldiers of the Kyiv garrison took place. They decided to consider themselves to be the Ukrainian Military Council, and in such status to direct an official request to the Provisional Government in Petrograd demanding autonomy for Ukraine. Within a week, the Ukrainian Military Club named aft er Hetman Pavlo Polubotok was founded in Kyiv. It took over the organization of their “own national army, the powerful military force, without which one cannot think of obtaining the full freedom of Ukraine”.Due to the appeal of the Polubotko Club members, Ukrainian soldiers initiated the creation of various self-gathered organisations on all fronts, armies and larger garrisons in the rear area. On 18 April 1917, more than 3,000 soldiers of the Kyiv redeployment depot declared themselves to be the 1st Ukrainian Cossack regiment named aft er Hetman Bohdan Khmelnytskyi. But the Russian command refused to recognise the regiment, having accused its soldiers of intentionally staying in the far rear zone and thus trying to avoid participation in hostilities. However, three days later, under pressure from the revolutionary situation, it was forced to agree to the formation of a 500-man Ukrainian volunteer military unit.In order to unite and channel the powerful but largely spontaneous Ukrainian patriotic movement in the Russian army, the 1st Ukrainian Military Congress was held in Kyiv on 5–8 May 1917. It was attended  by over 700 delegates, representing nearly one million soldiers. The delegates demanded autonomy for Ukraine within a federal Russian state as well as the “immediate nationalization of the army on the nationalterritorial principle”. Additionally, they demanded the Black Sea Fleet be replenished in future only by Ukrainians. Congress also raised the question of the introduction of the Ukrainian command language in the army. It should be used in national military units and schools.